What do primary school principals from the Yamaji region or Mid West Education District say about their school's bullying prevention and management guidelines and practices and how they support the strengths and needs of Aboriginal students and their families? - Paki, Dionne (2010)
Background: Australia‟s Aboriginal and Torres Strait Islanders are over represented in poor health and education outcomes. Little is known about the bullying experiences of Aboriginal school age children and young people. This Master's study aimed to investigate the policies and practises school principals use for bullying prevention and management in primary schools located in the Yamaji region or Midwest Education District of Western Australia.This study was conducted in conjunction with the Child Health Promotion Research Centre‟s Solid Kids, Solid Schools project. Solid Kids, Solid Schools is a four-year study that aimed to contextualise the bullying experiences of Yamaji school-age children and young people; and develop a locally relevant and culturally secure bullying prevention and management resource. Method: Thirty-one principals and four deputy principals of primary school aged students participated in either a semi-structured telephone interview or survey. Instrument items asked principals: how often staff at their school used 12 bullying management strategies; to describe and rate the effectiveness of 25 bullying prevention guidelines and strategies; and to describe enablers and barriers to working with Aboriginal students who are bullied or who bully others.Participant responses were matched for compliance with evidence-based recommendations (Cross, Pintabona, Hall, Hamilton, & Erceg, 2004, p. 11) and national policy as set out in the National Safe Schools Framework (NSSF) (Department of Education Science and Training; DEST, 2003) for school bullying prevention and management. Participant responses were also compared to a culturally secure bullying prevention and management model to determine if their guidelines and strategies are culturally secure and could respond to the strengths and needs of Aboriginal students